Analisis Pelanggaran Kode Etik Bankir di Indonesia: Kasus dan Implikasinya - Anissa Nur Silvia; Talitha Nisriinaa Almira; Neneng Weti Isnawaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The background of writing this article is the author's interest which arises from the understanding that in the complex dynamics of the professional world, maintaining integrity and ethics in every profession is an absolute obligation. This provides a foundation that ethics, especially those manifested in the professional code of ethics, are the main foundation for forming identity and public trust in a profession. However, reality shows that violation of the professional code of ethics are still a problem that needs to be fixed. The author needs to dig deeper to understand this phenomenon, identify concrete cases, and explore the various sanctions applied in response to such violations. This understanding should not only focus on the individual level but also include the collective impact on the overall reputation and integrity of the profession. Therefore, the author feels that discussing violations of the professional code of ethics and sanction are a crucial step to strengthen integrity and trust in the professional and organizational world.